2013
DOI: 10.1155/2013/976360
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Benzamide/Cholesterol Mixture by Using TLC/FTIR Technique

Abstract: We applied TLC/FTIR coupled with a mapping technique to analyze a cholesterol/benzamide mixture. Narrow-band TLC plates by using AgI as a stationary phase were used to separate benzamide and cholesterol. The distribution of cholesterol and benzamide spots was manifested by 3D chromatogram. Benzamide and cholesterol can be successfully separated by the narrow-band TLC plate. Moreover, characteristic bands of benzamide and cholesterol can be identified from their FTIR spectra. In addition, the FTIR spectra of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…To solve this problem, we proposed to use narrow band TLC plate in TLC/ IR analysis. 29 The results demonstrated that not only the amount of AgI used in the experiment is remarkably reduced, but also the performance of the TLC/IR analysis is signicantly improved by using narrow band TLC plate. Furthermore, the development of FTIR spectrometer with a microscope attachment has provided a new chance for the development of TLC/IR technique.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To solve this problem, we proposed to use narrow band TLC plate in TLC/ IR analysis. 29 The results demonstrated that not only the amount of AgI used in the experiment is remarkably reduced, but also the performance of the TLC/IR analysis is signicantly improved by using narrow band TLC plate. Furthermore, the development of FTIR spectrometer with a microscope attachment has provided a new chance for the development of TLC/IR technique.…”
Section: Introductionmentioning
confidence: 95%
“…Satisfactory results have been obtained. 29,30 All these work have demonstrated that TLC/FTIR by using AgI as stationary phase is applicable to real chemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, interações podem ocorrer resultando na mudança do número de onda das bandas de absorção, quando comparado aos espectros das mesmas amostras, analisadas diretamente por infravermelho [15] . Muitos trabalhos, incluindo alguns recentes, citam a aplicação de TLC-IR na análise in situ de multicomponentes, fazendo uso de microscopia FT-IR [14,16] . Entretanto este acessório é de uso restrito devido ao alto custo e tal qual a análise DRIFT, a fase estacionária pode interferir nas bandas de absorção do material.…”
Section: Introductionunclassified